High Performance Work System dan Leader-Member Exchange Terhadap Psychological Capital di Moderasi oleh Psychological Wellbeing - Rachman, Mochammad Jodhy Julia; Widhiastuti, Hardani; Erlangga, Erwin; Nunik Kusnilawati (Reswara Journal of Psychology, 2022)
This study aims to analyze the relationship between high performance work systems, leader-member exchange, psychological wellbeing and psychological capital. The number of samples taken as many as 74 respondents with purposive sampling technique. The validity of the sample was tested by loading factor and average variance extracted (AVE) while the reliability test used an internal consistency test based on Cronbach's Alpha and Composite Reliability. Validity test with loading factor and AVE value shows a valid value. The reliability tester with the internal consistency test has Cronbach's Alpha and Composite Reliability values that meet the criteria.The results showed that the high-performance work system had a positive and significant effect of 0.370 on psychological capital with a P value of 0.045. The leader-member exchange has a positive and significant effect of 0.225 on psychological capital with P-values of 0.037. Psychological well-being was significant as a moderating effect between high-performance work systems on psychological capital with a P-value of 0.028 and psychological well-being was significant as a moderating effect between leader-member exchange on psychological capital with a P-value of 0.006